2020
DOI: 10.1111/maec.12579
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation of abundant picoeukaryotes in the subtropical Kuroshio Current in winter

Abstract: To understand the importance of picoeukaryotes in the biogeochemical cycle in the subtropical Kuroshio Current, a year‐round survey of the hydrography and the distribution of picoeukaryotes were conducted in four oceanographic cruises from October 2012 to July 2013. In comparison with other seasons, the highest abundancy of photosynthetic picoeukaryotes, with concentrations >104 cells/ml, was observed around the eastern boundary of the Kuroshio in the winter. Accordingly, the composition of picoeukaryotes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…A thermal niche differentiation between MAST-1 subclades was observed. MAST-1D inhabit warm offshore waters, which is consistent with previous observations in Kuroshio water [34]. Also, our previous study revealed that the majority of MAST-1D sequences were retrieved from lower latitudinal regions [15].…”
Section: Discussionsupporting
confidence: 90%
“…A thermal niche differentiation between MAST-1 subclades was observed. MAST-1D inhabit warm offshore waters, which is consistent with previous observations in Kuroshio water [34]. Also, our previous study revealed that the majority of MAST-1D sequences were retrieved from lower latitudinal regions [15].…”
Section: Discussionsupporting
confidence: 90%
“…There, it was mostly dominated by Prochlorococcus and Synechococcus (Jiao and Yang, 2002;Li et al, 2017;Endo and Suzuki, 2019;Liu et al, 2020). The picoeukaryotes abundance was relatively low in a similar region, and its majority was composed of Alveolata, Haptophyta, and Stramenopiles (Chan et al, 2020). The abundance of total autotrophic picoplankton (Prochlorococcus + Synechococcus + picoeukaryotes) was significantly related to the Chl a concentration (Figure 6a).…”
Section: Coastal Uplift Impact On Biological Variables In the Kuroshiomentioning
confidence: 93%
“…and autofluorescence in the ranges of orange from phycoerythrin (575 ± 15 nm, for Synechococcus) and red from divinyl chlorophyll (>670 nm, for Prochlorococcus and photosynthetic picoeukaryotes) under excitation at 488 nm (Chan et al, 2020). The heterotrophic bacteria were stained with the nucleic acidspecific dye SYBR R Green I (emission = 530 ± 30 nm) in a 10 4 -fold-diluted commercial solution (Molecular Probes, Eugene, OR, United States; Liu et al, 2002).…”
Section: Biological Variables and Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…They were then identified and enumerated using a flow cytometer (FACSAria, Becton-Dickinson, East Rutherford, NJ, USA). The different picophytoplankton was distinguished based on cell size (forward- and side-scattering) and autofluorescence in the ranges of orange from phycoerythrin (575 ± 15 nm, for Synechococcus ) and red from divinyl chlorophyll (>670 nm, for Prochlorococcus and photosynthetic picoeukaryotes) under excitation at 488 nm [ 51 ]. The heterotrophic bacterioplankton was stained with the nucleic acid-specific dye SYBR ® Green I (emission = 530 ± 30 nm) in a 10 4 -fold-diluted commercial solution (Molecular Probes, Oregon, USA) [ 52 ].…”
Section: Methodsmentioning
confidence: 99%